2022
DOI: 10.1111/ijac.14270
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis of Bi2O3–YSZ composite powders and their sintering behavior for high‐performance electrolytes

Abstract: Bismuth oxide (Bi 2 O 3 ) is a promising additive to decrease the sintering temperature of yttria-stabilized zirconia (YSZ)-based electrolyte for solid oxide fuel cell application. However, Bi 2 O 3 tends to grow into large column bars (>50 µm) in a chemical coprecipitation method, which dramatically limits the mixing uniformity of Bi 2 O 3 and YSZ, even much worse than that of mechanical mixing. In this study, the reaction temperature was increased from room temperature to 90 • C to increase the number of nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Additionally, doping with Bi 2 O 3 and CuO can have favorable effects on sintering, but with limitations induced by the destabilization of the crystalline structure of YSZ [117,118].…”
Section: Zirconia-based Materialsmentioning
confidence: 99%
“…Additionally, doping with Bi 2 O 3 and CuO can have favorable effects on sintering, but with limitations induced by the destabilization of the crystalline structure of YSZ [117,118].…”
Section: Zirconia-based Materialsmentioning
confidence: 99%
“…A study had been conducted by using 8 mol% Lu 2 O 3 doped 8YSZ and successfully improved the flexural strength of the materials without compromising the ion conductivity [30]. Other studies on the dopant like CuO, TiO 2 and Bi 2 O 3 , also reported the sintering aids for 8YSZ effectively aided the ceramics material to reach full densification at a lower sintering temperature without compromising ion conductivity [31][32][33]. Lower sintering temperature for full densification, which is highly related to the mechanical properties like hardness and fracture toughness, means less energy required during processing.…”
Section: Figure 14mentioning
confidence: 99%
“…In addition, the melting point of Bi 2 O 3 , which is commonly used as a liquid-phase-assisted sintering additive for YSZ to enhance its overall performance, is around 825 °C [ 19 , 20 ]. By mechanically mixing Bi 2 O 3 with YSZ or synthesizing Bi 2 O 3 -doped YSZ composite powders, our group and other researchers have demonstrated its effectiveness in lowering the sintering temperature of YSZ electrolytes [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%